IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH PADA MATA PELAJARAN MATEMATIKA DI SMP NEGERI 3 KAMPAK: SMP NEGERI 3 KAMPAK KABUPATEN TRENGGALEK - SUWARNO SUWARNO (Dewan Pendidikan Bondowoso, 2021)
Mathematics as one of the subjects in school that is important in shaping students to be qualified, because mathematics is a means of thinking to examine everything logically and systematically. Therefore, it is necessary to improve the quality of education in the field of mathematics. It is very important to give students the breadth to gain experience and understanding of the information obtained from the problems around them. The learning model in question is a problem-based learning model which is a learning model based on constructivist understanding that accommodates student involvement in authentic learning and problem solving. This research is devoted to the class VIII A of SMP Negeri 3 Kampak, totaling 22 students in mathematics with basic competencies explaining a system of two-variable linear equations and their solutions associated with contextual problems. The results of this study are the implementation of the Problem-Based Learning model runs smoothly and in accordance with the syntax even though there are several obstacles as follows, 1) students are not familiar with the form of problem-based questions, 2) students need to add experience solving problems, especially those related to everyday life. them, 3) need to get used to discussing and solving problems